The Role of Advertising in Changing Concentration of Manufacturing Industries - Mueller, Willard F.; Rogers, Richard T. (The Review of Economics and Statistics, 1980)
T HERE is increasing evidence that advertising plays an especially prominent role in structural change.' Mueller and Hamm (1974) found that between 1947 and 1970 concentration was increasing the most in industries characterized by a high degree of product differentiation. In reworking the Mueller-Hamm study because he felt that their model suffered from regression bias, Wright (1978) substantiated the Mueller-Hamm conclusions. Ornstein and Lustgarten (1978) found changes in industry advertising-to-sales ratios to be a significant positive variable in a model that explains changing industry concentration, although they are quite cautious in interpreting their findings. Here we add to previous work by reporting the major results from an analysis of changes in industry concentration based on a sample of 167 four-digit Standard Industrial Classification (SIC) industries for which comparable data were available for the period 1947 to 1972.2 Starting with a slightly modified Mueller-Hamm model we extend the analysis by replacing the dummy variable classification scheme for the degree of product differentiation developed by Parker (1967) with a continuous measure of advertising intensity.3 We then differentiate between television and other types of media advertising.